Analysis of preferred weight configuration for barebow shooting style - Pietra, F.; Loveday, P.; Reid, R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
The barebow archery shooting style limits the stabilisation system to weights connected to the riser, which is the central part of the bow. No scientific study is available to guide the barebow archer in the choice of the best weight configuration. In the following work, a human-centred methodology was developed to address this problem from both a scientific and user-oriented perspective. The proposed methodology is based on subjective metrics (archers` sensations using the equipment), objective metrics (measurable quantities) and precision. The study sought a correlation between the subjective and objective metrics to provide insight into the problem of configuring a bow. Eleven weight configurations were considered. The vibration was measured at five positions on the bow and the 3D dynamic motion was measured using an inertial measurement unit. Seven archers completed a questionnaire to evaluate the subjective shooting sensations. The results show that the two best weight configurations are the 250-200 g and the 350-200 g, at the central and lower attachment points, respectively. A strong correlation exists between the vibration level of the bow and the feeling archers associated with the shooting, and between the dynamic motion of the bow and the comfort of the shooting. No correlation was found between the vibration time and the physical sensations felt by the archers. Determining the influence of the weight configuration on shooting accuracy, with statistical significance, would require an impractically large number of arrows to be shot for each weight configuration. A new methodology was developed to correlate the archers` physical sensations to measurable parameters and this was applied to understand the barebow weight selection problem. This methodology could be further developed to correlate additional subjective and objective metrics. An understanding of these correlations would allow objective metrics, which can be simulated in the design process, to be used to ensure satisfaction of subjective metrics by the final design.